2018
DOI: 10.3758/s13421-018-0877-6
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trends in lineup performance: Adolescents are more prone to innocent bystander misidentifications than children and adults

Abstract: We tested developmental trends in eyewitness identification in biased and unbiased lineups. Our main interest was adolescent's lineup performance compared with children and adults. 7-10-year-olds, 11-13-year-olds, 14-16-year-olds, and adults (N = 431) watched a wallet-theft-video and subsequently identified the thief, victim, and witness from simultaneous target-present and targetabsent six-person photo lineups. The thief-absent lineup included a bystander previously seen in thief proximity. Research on uncons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…Descriptively, adolescents gave don't know answers least often, and this difference was statistically significant compared to children, but not compared to adults. This is in line with a study in which adolescents had difficulties in rejecting a lineup that contained a bystander, compared to adults and children (Brackmann, Sauerland, & Otgaar, 2018). This outcome may be due to reduced executive control processes (Luciana et al, 2005) and more impulsive decision making in adolescents than children (Gardner & Steinberg, 2005;Nigg, 2000;Steinberg et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…Descriptively, adolescents gave don't know answers least often, and this difference was statistically significant compared to children, but not compared to adults. This is in line with a study in which adolescents had difficulties in rejecting a lineup that contained a bystander, compared to adults and children (Brackmann, Sauerland, & Otgaar, 2018). This outcome may be due to reduced executive control processes (Luciana et al, 2005) and more impulsive decision making in adolescents than children (Gardner & Steinberg, 2005;Nigg, 2000;Steinberg et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…The confidence accuracy association is discernible for older children, young adults, and older adults. For young children, high confidence was less clearly associated with accuracy, which echoes earlier findings (Brackmann et al, 2019). However, the novelty of our findings is that the lack of association between confidence and accuracy in young children only appears to be true in the first line-up position.…”
Section: Confidence Accuracy Characteristicsupporting
confidence: 76%
“…Although there is an ongoing debate regarding the superiority of either sequential or simultaneous line-ups (e.g., Wells et al, 2015), research on line-up position effects has not been very consistent, and within both sequential line-ups (e.g., Wilson et al, 2019) and simultaneous line-ups (Clark and Davey, 2005;Palmer et al, 2017;Meisters et al, 2018;Carlson et al, 2019), previous findings vary. Moreover, in eyewitness research, age comparisons are not very common and focused on young adults, with less focus on children, adolescents, and older adults (Erickson et al, 2015;Fitzgerald and Price, 2015;Brackmann et al, 2019). We were also unable to find an investigation of age and position effects, despite earlier findings showing that children and older adults tend to produce more false alarms in target absent line-ups (Bartlett and Memon, 2007;Bartlett, 2014;Fitzgerald and Price, 2015).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The few studies of the relation between children's confidence and accuracy on photo lineups reveal that, overall, young children's confidence ratings are not predictive of their lineup accuracy (e.g., Brackmann et al 2019;Humphries and Flowe 2015), and children tend to be overconfident in their abilities (Brewer and Day 2005;Keast et al 2007;), just as the classic adult findings. Little is known about moderators of this relation, but Bruer and Price (2017) found that, across different lineup procedures, greater confidence predicted better accuracy among older (vs. younger) children for choosing a suspect from a lineup (but not for rejecting a lineup).…”
Section: )?mentioning
confidence: 99%